Batik di Era Teknologi Digital - Djandjang Purwo Sedjati (Ars: Jurnal Seni Rupa dan Desain, 2011)
Batik in the Era of Digital Technology. The processof Batik making (handmade batik and printed batik)operates certain techniques and equipments that arecertainly influenced by the technology development. Theeffects do not only touch the production process but alsothe distribution process. Digital technology is also appliedin this field that in one way or another promotes thebatik art. Digital technology is already used in creatingbatik design. It results in various type of design, forexample the fractal batik that makes over the geometricalforms. Digital technology applied in designing batikcauses a more effective and efficient making process.This technology completes the manual process that is stillemployed until today.